The Effect of Perceptions of Maxim Car Service Quality on User Decisions on the Maxim Application: Pengaruh Persepsi Kualitas Pelayanan Maxim Car Terhadap Keputusan Pengguna pada Aplikasi Maxim - Putri, Annisa Krismalia (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Studi Islam Sunan Doe, 2023)
This research was conducted to determine the effect of perceived service quality on user decisions in choosing to use the Maxim application. This is to see how much influence maxim's service quality has on user decisions. There are many applications with the same service as Maxim, but why do users prefer to use Maxim's services. This study uses a quantitative method with a quantitative survey design. The population in this study were maxim car users, the sample used was 100 respondents using purposive sampling. The research instrument used a questionnaire. There is an R Square value of 0.654, meaning that 65.4% of the variable perceived service quality can influence user decisions, while other factors or variables influence the remaining 34.6%. The simple linear regression test shows that the magnitude of F count = 184.866 > F table = 3.947. The a and b values of the general regression equation are Y=a+bx, so we get -5.282+1.671x. As well as, the sig value obtained is 0.000, which means it is smaller than 0.05. Thus it can be concluded that there is a positive and significant influence between the perception of the quality of Maxim car service on the decisions of Maxim application users.